Dissolved organic matter and its correlation with phytoplankton abundance for monitoring surface water quality - O. Cahyonugroho; S. Hariyanto; G. Supriyanto (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Dissolved organic matter has a fundamental role in supporting phytoplankton abundance and growth in aquatic environments. However, these organisms produce dissolved organic matter with varied quantities or characteristics depending on the nutrient availability and the species composition. Therefore, this study aims to assess the characteristic of dissolved organic matter on surface water and its correlation with phytoplankton abundance for monitoring water quality.METHODS: The sample was obtained at four Kali Surabaya River stations for further dissolved organic matter analysis and phytoplankton species analysis. The analysis was presented through bulk parameters of total organic, ultraviolet at 254 nm wavelength (UV254), specific ultraviolet absorbance value, and fluorescence spectroscopy using excitation-emission matrices with fluorescence regional integration analysis.FINDINGS: The results showed the bulk parameters of dissolved organic matter at all stations were significantly different, as Station 1 and 2 were higher, while 3 and 4 had a lower concentration. Furthermore, the fluorescence spectroscopy identified four components of dissolved organic matter at all stations, namely aromatic proteins-like (AP-like), humic acid-like (HA-like), soluble microbial by-products-like (SMPs-like), and fulvic acid-like (FA-like). Also, stations 1 and 2 were grouped in the high percentage FRI of humic substance (FA-like and HA-like), while 3 and 4 were classified in the high percentage FRI of non-humic substances (AP-like and SMPs-like).CONCLUSION: The main phytoplankton species, namely Plectonema sp., Pinularia sp., Nitzchia sp., Navicula sp., had the highest abundance at Stations 1, 3, and 4, respectively. A strong correlation between dissolved organic matter analysis and phytoplankton abundance led to the usage of these methods for monitoring surface water quality.